Time of permanence in the bloodstream and biodistribution of MnFe2O4 in rats: Preliminary results - Próspero, A. G. [UNESP]; Fidelis-De-Oliveira, P. [UNESP]; Quini, C. C. [UNESP]; De Gobbi, J. [UNESP]; Matos, J. F. [UNESP]; Zufelato, N.; Bakuzis, A. F.; Miranda, J. [UNESP] (Springer Nature, 2015)
The Association between nanotechnology and biomagnetic diagnostic techniques unwrapped a whole new research field that allows us to noninvasively study physiological parameters, such as dynamic perfusion and retention in organs and tissues. By associating the AC Biosusceptometry (ACB) system to magnetic iron oxide nanoparticles doped with manganese, we analyzed circulation time and biodistribution patterns for these particles after 20 minutes of infusion. We found a circulation time of 181±49 s, with major biodistribution to liver, lungs and spleen, given the particles features and the organs morphology. Our results showed the ACB system efficiency on particles dynamic tracing and bloodstream patterns assessments, and suggest the use of less reactive nanoparticles with a higher circulation time in the body.
Keywords: AC Biosusceptometry; Biodistribution; Biomagnetism; Cardiac perfusion and magnetic nanoparticles; Manganese ferrite